2018
DOI: 10.17221/792/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of selected fungi of the soil environment of carrot

Abstract: The present studies aim at determining the antagonistic effect of selected fungi species occurring in the soil under carrot cultivation towards Altenaria dauci (J.G. Kühn) J.W. Groves & Skolko, Alternaria radicina Meier, Drechsler & E.D. Eddy, Fusarium oxysporum E.F. Sm & Swingle, Rhizoctonia solani J.G. Kühn and Sclerotinia sclerotiorum (Lib.) de Bary. The field experiment considered cover crops (oats, tansy phacelia and vetch). The control consisted of traditional carrot cultivation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
4
0
3
Order By: Relevance
“…These bacteria and fungi (especially Trichoderma spp.) have a considerable influence on plant health [61][62][63]. They inhibit the growth and development of phytopathogens in the soil through antibiosis, competition, and parasitism [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria and fungi (especially Trichoderma spp.) have a considerable influence on plant health [61][62][63]. They inhibit the growth and development of phytopathogens in the soil through antibiosis, competition, and parasitism [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…Tolerance to Fusarium crown and root rot appeared in the practical decline soil. The effect of AMF species, especially G. intraradices, demonstrated the highest effectiveness as a biocontrol agent [19][20][21]. Smith and Read [1] show the phenomenon of synergetic pathogen bio-control by simultaneously using mycorrhiza and saprotrophic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…are considered good antagonists. Patkowska et al [21] conducted laboratory tests that demonstrated the antagonistic properties of Panicillium spp. against F. oxysporum isolated from carrot soil.…”
Section: Discussionmentioning
confidence: 99%
“…Перші докази того, що різні види Tuber мають симбіотичні зв'язки з коренями їх господарів було отримано в 60-х роках ХХ ст. [5,6,7,12,17,19,22]. У багатьох країнах трюфелі мають великий попит, завдяки їх специфічному запаху і смаку [11,13,15,16].…”
Section: вступunclassified
“…Поглинальна здатність кореня рослини збільшується завдяки тому, що гіфи мають ширший радіус та швидкість поширення, ніж кореневі волоски, а також здатні поглинати поживні речовини у низьких концентраціях. Особливо важливе значення має мікориза у покращенні фосфорного живлення [2,3,4,9,17,21]. Рослина отримує фосфор у вигляді поліфосфатів через гіфи мікоризних грибів.…”
Section: вступunclassified